2022
DOI: 10.1002/aoc.6629
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and anticancer activity of ferrocenyl complexes bearing different organopalladium fragments

Abstract: A straightforward synthetic route to a selection of new ferrocenyl complexes bearing different organopalladium fragments is reported. The target complexes were fully characterized by Nuclear Magnetic Resonance, High Resolution Mass Spectrometry, Infrared Spectroscopy, X‐ray Diffraction, and electrochemical techniques. All compounds, with the exception of Pd(0)‐olefin derivatives, showed excellent antitumor activity on ovarian cancer cells and, in the case of Pd (II)‐allyl and Pd (II)‐butadienyl complexes, a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…The main drawback of palladium complexes is the rapid hydrolysis in aqueous medium compared with platinum derivatives. A good solution to this problem is the use of ligands firmly anchored to the metal center, and, among these, organopalladium derivatives, by virtue of the presence of at least one strong Pd–C bond, have so far provided the best results . In this context, Scattolin and Visentin have recently described the remarkable cytotoxicity of cationic NHC-Pd­(II)-η 3 -allyl complexes .…”
Section: Biologically Active Metal-n-heterocyclic Carbene Complexesmentioning
confidence: 99%
“…The main drawback of palladium complexes is the rapid hydrolysis in aqueous medium compared with platinum derivatives. A good solution to this problem is the use of ligands firmly anchored to the metal center, and, among these, organopalladium derivatives, by virtue of the presence of at least one strong Pd–C bond, have so far provided the best results . In this context, Scattolin and Visentin have recently described the remarkable cytotoxicity of cationic NHC-Pd­(II)-η 3 -allyl complexes .…”
Section: Biologically Active Metal-n-heterocyclic Carbene Complexesmentioning
confidence: 99%
“…Also our group has been involved in this topic, preparing and testing as anticancer agents, a large number of organopalladium complexes. The organometallic motifs by us so far examined included Pd(II)-allyls, [21][22][23][24][25][26][27] palladacyclopentadienyls, [27,28,29] Pd(0)-olefins [27,30] and more recently Pd(II)-indenyls, [31][32][33] while other research groups turned their attention to Pd(II)-alkynyls [34] and an extensive panel of cyclopalladates. [19,[35][36][37][38] All these works indicate the primary importance of the organic fragment in determining the activity of the complex although it can be modulated by a careful choice of the ancillary ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has recently proposed a systematic study of the antiproliferative activity towards ovarian cancer cells of different organopalladium derivatives coordinating dppf, obtaining interesting responses. [27] Ultimately, the aim of this work is the preparation of a series of new Pd-imidoyl complexes coordinating PTA, DAPTA and dppf, with a preliminary study of their antiproliferative and proapoptotic activity towards ovarian cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, no study has been reported in the literature about the biological properties of palladium complexes equipped with tertiary alkyl isocyanides [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], and our choice to test the anticancer activity of Pd(II)-indenyl and Pd(II)-allyl complexes supported by these kinds of ligands is intended to begin filling this gap.…”
Section: Introductionmentioning
confidence: 99%